The Effect of Leadership and Ethics on Motivation in the Military - Sukmadi, Bambang Heru (International Humanities and Applied Science Journal, 2019)
This research aims to explore and find out the effect of leadership and ethics on the motivation of the soldiers of the Indonesian military. The research is conducted on the soldiers in the rank of non-commissioned and enlisted (Sergeant, Corporal and Private) at one of the Indonesian military units in Jakarta. The data is obtained with the survey method on the sample that comprises of 83 respondents. A simple random sampling technique is used to take the sample among the soldiers in the unit. The data is analyzed with the Path Analysis technique utilizing SPSS 22 software. The questionnaires as the instrument of research are validated with Product Moment correlation while the reliability of instruments is measured with Alpha Cronbach. The test of validity and reliability is applied to 30 respondents. The findings of the research are (1) leadership has a positively direct effect on motivation; (2) military ethics has a positively direct effect on motivation; (3) leadership and military ethics have a simultaneously positive effect on motivation.Â Based on the findings, the motivation of soldiers can be enhanced by strengthening leadership and military ethics. The motivation is more enhanced by ethics than leadership. The enhancement of motivation is prioritized on the weakest aspect of motivation namely the desire to affiliate. Accordingly, strengthening ethics is prioritized on the consistency of applying the code of ethics as the weakest aspect of ethics and strengthening leadership is prioritized on influencing ability which are the weakest aspects of leadership